Analisis Determinan Perkembangan Bahasa pada Anak Usia Toddler dengan Paparan Screen Time - Fitriana Fitriana; Nani Nurhaeni; Robiyatul Adawiyah; Isran Isran (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2026)
Significant challenges have emerged alongside the massive exposure to digital technology or screen time in early childhood. Children aged 1–4 years in Indonesia have been exposed to smartphones that 37.02%. The prevalence reaches over 70%, signaling In urban areas that many parents have not complied with the recommended limitations. Toddler tend to be exposed to electronic devices or screen time in this technological era and this is a challenge for parents regarding children's language development. The aim of this research is analyze the factors that influence the language development of toddler who are exposed to screens time in East Jakarta. This research uses a crosssectional design. Sample selection was using cluster random sampling and studied on 200 respondents. This research was conducted on children aged 1-3 years who were exposed to screen time every day. The instrument in this study used CLAMS to assess language development. The statistical test used is ordinal logistic regression. The results of this research show that there was a significant between birth history, duration of screen time exposure, parental education and stimulation. The dominant variable is stimulation. The conclusion is the language development of toddler who are exposed screen time will remain normal if balanced with stimulation. The recommended of this research that language development examinations be carried out simultaneously with posyandu services in order to detect and intervene early in language development delays